Efficient thermal dissipation in wafer-scale heterogeneous integration of single-crystalline β-Ga2O3 thin film on SiC - Wenhui Xu; Tiangui You; Yibo Wang; Zhenghao Shen; Kang Liu; Lianghui Zhang; Huarui Sun; Ruijie Qian; Zhenghua An; Fengwen Mu; Tadatomo Suga; Genquan Han; et al. (Fundamental Research, 2021)
The semiconductor, β-Ga2O3 is attractive for applications in high power electronic devices with low conduction loss due to its ultra-wide bandgap (∼4.9 eV) and large Baliga's figure of merit. However, the thermal conductivity of β-Ga2O3 is much lower than that of other wide/ultra-wide bandgap semiconductors, such as SiC and GaN, which results in the deterioration of β-Ga2O3-based device performance and reliability due to self-heating. To overcome this problem, a scalable thermal management strategy was proposed by heterogeneously integrating wafer-scale single-crystalline β-Ga2O3 thin films on a highly thermally conductive SiC substrate. Characterization of the transferred β-Ga2O3 thin film indicated a uniform thickness to within ±2.01%, a smooth surface with a roughness of 0.2 nm, and good crystalline quality with an X-ray rocking curves (XRC) full width at half maximum of 80 arcsec. Transient thermoreflectance measurements were employed to investigate the thermal properties. The thermal performance of the fabricated β-Ga2O3/SiC heterostructure was effectively improved in comparison with that of the β-Ga2O3 bulk wafer, and the effective thermal boundary resistance could be further reduced to 7.5 m2K/GW by a post-annealing process. Schottky barrier diodes (SBDs) were fabricated on both a β-Ga2O3/SiC heterostructured material and a β-Ga2O3 bulk wafer. Infrared thermal imaging revealed the temperature increase of the SBDs on β-Ga2O3/SiC to be one quarter that on the β-Ga2O3 bulk wafer with the same applied power, which suggests that the combination of the β-Ga2O3 thin film and SiC substrate with high thermal conductivity promotes heat dissipation in β-Ga2O3-based devices.